Plastic and Reconstructive Surgery in the Treatment of Oncological Perineal and Genital Defects - Brodbeck, Rebekka; Horch, Raymund E.; Arkudas, Andreas; Beier, Justus P. (Frontiers in Oncology, 2015)
Defects of the perineum may result from ablative procedures of different malignancies. The evolution of more radical excisional surgery techniques resulted in an increase in large defects of the perineum. The perineogenital region per se has many different functions for urination, bowel evacuation, sexuality and reproduction. Up-to-date individual and interdisciplinary surgical treatment concepts are necessary to provide optimum oncological as well as quality of life outcome. Not only the reconstructive method but also the timing of the reconstruction is crucial. In cases of postresectional exposition of e. g. pelvic or femoral vessels or intrapelvic and intra-abdominal organs, simultaneous flap procedure is mandatory. In particular, the reconstructive armamentarium of the plastic surgeon should not only include pedicled, but also free microsurgical flaps so that no compromise in terms of the extent of the oncological resection has to be accepted. For intra-abdominally and/or pelvic tumors of the rectum, the anus or the female reproductive system, which were resected through an abdominally and a sacrally surgical access, simultaneous VRAM flap reconstruction is recommendable. In terms of soft tissue sarcoma of the pelvic / caudal abdomen / proximal thigh region, two-stage reconstructions are possible. This review focuses on the treatment of perineum, genitals and pelvic floor defects after resection of malignant tumors, giving a distinct overview of the different type of defects faced in this region and describing a number of reconstructive techniques, especially VRAM flap and pedicled flaps like ALT flap or free flaps. Finally, this review outlines some considerations concerning timing of the different operative steps.